Corrosion characteristics of tapered sleeve locking-type splicing reinforcement in precast segmental bridge piers. (February 2023) - Wang, Jian; Wang, Zetao; Du, Jinsheng
Abstract: Tapered sleeve locking-type splicing (TSLTS) reinforcement joint is a new type and efficient way of mechanical reinforcement connection, which can be used for connecting of longitudinal steel bars in precast segmental bridge (PSB) piers. Since the TSLTS reinforcement joints are located at the bottom zone of the PSB piers, the PSB piers are often poured with self-compacting concrete (SCC) in this part, which is a new and convenient construction method of PSB piers. In this paper, the corrosion characteristics of TSLTS reinforcement in PSB piers in coastal environment were investigated. Through the accelerated corrosion test, the connection performance of corroded TSLTS reinforcement joints was studied. Then, the corrosion characteristics of TSLTS reinforcement in SCC segment and ordinary Portland concrete (OPC) segment of the PSB piers were discussed, and effect of the interface between the two segments on the corrosion of TSLTS reinforcement was analyzed. The results showed that the critical mass loss for slip failure of TSLTS reinforcement joints was about 7.2%. The mean mass loss of TSLTS reinforcement in SCC segment was larger than that of TSLTS reinforcement in OPC segment, and the corrosion rate of TSLTS reinforcement joints in SCC segment was about 1.54 times that of TSLTS reinforcement in OPC segment. The uneven corrosion coefficient of the TSLTS reinforcement joint was the largest, which increased first and then decreased with the increase of corrosion time. The uneven corrosion coefficient of TSLTS reinforcement in SCC segment was approximately equal to that of in OPC segment, and the uneven corrosion degree of the TSLTS reinforcement joint was about 1.98 times that of TSLTS reinforcement in SCC segment. The mean mass loss of TSLTS reinforcement at the interface was greater than those of in SCC and OPC segments, and the pitting corrosion of TSLTS reinforcement at the interface was more serious. However, with the increase of corrosion time, the uneven corrosion coefficient of TSLTS reinforcement at the interface tended to be equal to those of TSLTS reinforcement at other parts (except the joint). The research results can provide references for the popularization and application of the TSLTS reinforcement joints in PSB piers in coastal environment.